Brain activations evoked by passive and active listening: a preliminary study on multiple subjects - Ahmad Nazlim Yusoff,; Mazlyfarina Mohamad,; Mohd Mahadir Ayob,; Mohd Harith Hashim, (Penerbit UKM, 2008)
A functional magnetic resonance imaging (fMRI) study was conducted on 4 healthy male and female subjects to investigate brain activation during passive and active listening. Two different experimental conditions were separately used in this study. The first condition requires the subjects to listen to a simple arithmetic instruction (e.g. one-plus-two-plus-three-plus-four) – passive listening. In the second condition, the subjects were given the same series of arithmetic instruction and were required to listen and perform the calculation – active listening. The data were then analysed using the Statistical Parametric Mapping (SPM5) and the MATLAB 7.4 (R2007a) programming softwares. The results obtained from the fixed (FFX) and random effects analyses (RFX) show that the active-state signal intensity was significantly higher (p < 0.05) than the resting-state signal intensity for both conditions. The results also indicate significant differences (p < 0.001) in brain activation between passive and active listening. The activated cortical regions during passive listening, as obtained from the FFX of the first condition is symmetrical in the left and right temporal and frontal lobes covering the cortical auditory areas. However, for the second condition, which was active listening, more activation occurs in the left hemisphere with a reduction in the number of activated voxels and their signal intensity in the right hemisphere. Activation mainly occurs in the middle temporal gyrus, precentral gyrus, middle frontal gyrus, superior temporal gyrus and several other areas in the frontal lobes. The point of maximum signal intensity has been shifted to a new coordinates during active listening. It is also observed that the magnetic resonance signal intensity and the number of activated voxel in the right and left superior temporal lobes for the second condition have been reduced as compared to that of the first condition. The results obtained strongly suggest the existence of functional specialisation. The results also indicate different networks for the two conditions. These networks clearly pertain to the existence of functional Jurnal Sains Kesihatan Malaysia 6 (1) 2008: 35-6036 connectivity between activation areas during listening and listening while performing a simple arithmetic task.